Intelligent Control based Estimation Techniques to enhancement secure data transfer rate in Microwave channel for Iraq Electrical Grid - Hoomod, Haider K.; Gulim, Mohammed R. (International Journal of Engineering and Technology, 2018)
The needed for broadband in wireless services is rapidly growth day after day (like internet or radio broadcast and TV etc.) for this reason and other to optimal exploiting this bandwidth may be other reasons indeed be there is problem (like bad weather) in the communications channel. it's necessary that employ the good part form this bandwidth to send our important data. In this paper, we propose to use estimation technique for estimate channel availability in that moment and next period to know the error in the bandwidth channel for controlling the possibility data transferring through the channel. The proposed estimation based on the combination of the Least Mean Square (LMS), Standard Kalman filter(SKF), and Minimum Mean Square Error (MMSE). The estimation error in channel uses as input for fuzzy logic bases rules to adapt the rate and size send data through the network channel, and rearrange priorities of the buffered data (power stations control parameters, voice, image, and video camera) for the bad cases of errors in channel then apply AES (Advanced Encryption Standard) algorithm to secure our data over wireless connection ( Microwave channel) . The propose system is designed to manage and secure data communications through the channels connect between the Iraqi electrical grid stations. The proposed results in the packets loss rate is reduced with ratio from (35% to 385%) The channel capacity is increase by 3 times.